PEMBUATAN SABUN KESEHATAN BERBAHAN DASAR MINYAK KAYU PUTIH DI MASA PANDEMI COVID-19 BAGI WALI MURID TK AISIYAH SERPONG, BANTEN - Fitriani Fitriani; Fitri Yuniarti; Wahyu Hidayati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
During the COVID-19 pandemic, there were several effects on people's economies that led to a decrease in household income. One way that can be done to improve the household economy is by producing products that are easy to make using household ingredients, among which are health soaps. Eucalyptus oil are very easy to trace in Indonesian society and have known benefits for health, so making health soap using eucalyptus oil and betel leaves can be a solution to improve the household economy. This activity was conducted by providing information about the benefits of eucalyptus oil followed by providing training on making health soap to the parents of TK Aisiyah Serpong, Banten. The results of this activity are shown by the enthusiasm of the participants when knowing the ease of making health soap. With this activity, participants are expected to produce health soap and make it as one way to improve the household economy